Comparison of the Effects of Mucosa Tissue Healing with Chlorhexidine Digluconate and Choline Salicylate in Patients Wearing a Removable Prosthetic Restoration—A RCT - Barbara Sekuła-Kamińska; Aleksandra Nitecka-Buchta; Mateusz Wojciechowski; Małgorzata Skucha-Nowak; Małgorzata Rymarczyk; Stefan Baron (Clinics and Practice)
Background and Objectives: A randomized, double-blind clinical trial was conducted based on the CONSORT study protocol for randomized clinical trials (NCT06531720) to compare the effectiveness of oral mucosa healing properties of 0.2% chlorhexidine digluconate (CHX) and 8.7% choline salicylate (CHS), as well as a control group (CON) with no intervention, in patients with delivered partial removable dentures (PRDs). Materials and Methods: Patients (n = 27) who were enrolled in the study were healthy subjects according to the inclusion/exclusion criteria, and they received new PRDs to complement Kennedy’s class III and IV deficiencies. During the process of adaptation to new prosthetic restorations, OMLs were formed and treated with one of two selected preparations, either CHX = 0.2% or CHS = 8.7%, in relation to the control group (CON). The wound surface area (WSA) (mm2) was measured on repeatable intraoral images taken in accordance with the examination protocol on the first control visit on day 1, day 3, day 7, day 10, and day 14 with the assistance of computer software. Results: There were no statistically significant differences between groups. The fastest effect of WSA complete reduction was observed in the CHX group after 7 days (WAS = 0.78, SD = 1.18) in comparison to CHS = 10 days (WAS = 0.44, SD = 0.90) and CON = 14 days (WAS = 0.22, SD = 0.67). The decrease in the WSA after 7 days of observation was 85.1% in the CHX group, 70.1% in the CHS group, and 59.2% in the CON group. Conclusions: The WSA decreased most rapidly after 7 days of treatment with 0.2% chlorhexidine digluconate (CHX), slightly more slowly after 10 days of treatment with 8.7% choline salicylate (CHS), and relatively most slowly in the CON group, who were not treated with any topical medication after 14 days. Oral mucosa lesions (OMLs) therapy during the process of adaptation to new removable prosthetic restorations is a very important element supporting the whole process. Topical medications containing 0.2% chlorhexidine digluconate are indicated as adjunctive therapy in the process of the supportive treatment and disinfection of oral mucosa lesions. However, this does not release the dentist from liability for the careful adjustment of the removable prosthetic restoration.